Trabalhadores de Call Centers: trabalho precário e resistências na Paraíba - Moraes, Ana Carmen Navarro de (2018)
This research has as object the forms of resistance developed by call center workers in Paraíba (from their individual manifestations to union actions), in the face of the process of spatial reconfiguration of the teleactivity centers underway in the country, in which business strategies operate in convergence with state actions in order to attract investments. Of qualitative nature, the data presented come from semi-structured interviews with telemarketers from companies located in Paraíba and local union leaders (directors and basic delegates) and from direct observation of daily life and union activities. Despite the conformation of adverse contexts to resistance, which tend to have individual expressions and reduced reach / effectiveness, we observe elements that are in opposition to the official discourse of greater commitment of Northeastern workers, such as the increasing dissemination of practices of disrespect to rules, breach of labor control standards and direct confrontational actions inside and outside the workplace, as well as the holding of protests / stoppages and specific activities of the call center sector, promoted by telecommunication syndicalism. The links between the daily resistance of workers and the reconfigurations of union action in the sector, although permeated by conflicts, especially those of generational nature, point to a process of (re) construction of representations of telecommunications workers in the context of Paraíba state, which seems to be contributing, along with the technological innovations promoted by the call center companies, to a cooling off of the expansion of the telemarketing operator's vacancies in Paraíba, despite the permanence of the territorial incentives of the local public power.